Intelligent Resource Allocation and Capacity Computation through RaI Representation in the Cloud using Deep Learning Techniques - Banda, Santhoshini; Murthy, A.Sampath Dakshina; Revathi, Bommideni; Challa, Narasimham (International Journal of Psychosocial Rehabilitation, 2020)
There are some situations where cloud computing is used to enhance the ability to the business goals, when and where to offload the resources like hardware, software, networks to cloud. So that one can offload the resources for processing as image based computation includes segmentation, deep learning for object recognition. Intelligent Agent algorithm also uses to collect performance metric in continuous period of time. Dynamic cloud allocation mechanism is implemented in processing of images parallelly. By adopting suitable mechanism one can automatically add images to cloud in real-time to know the number of available cloud instances. Queue length can be known with this. The proposed intelligent cloud resource procedure through RaI (Resources as Images) in the cloud improves overall response time, optimal utilization of cloud in order to access, allot and to determine the capacity of the resources.